The The Effect of Profitability, Debt Policy, and Investment Decisions on the Value of Insurance Companies Listed on the Indonesia Stock Exchange (2019-2023) - Iktiarni; Riyanti (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study analyzes the effect of profitability (ROE), debt policy (DER), and investment decisions (PER) on company value (PBV) in the Indonesian insurance sub-sector (IDX, 2019-2023) using multiple linear regression and secondary data from company financial reports. The regression analysis shows a positive and significant effect of profitability (ROE) and a negative and significant effect of debt policy (DER) on company value (PBV). Investment decisions (PER), although showing a positive effect, are not statistically significant. The model explains 66.5% of the variance in PBV. These findings have practical implications for investors, insurance company management, and regulators in investment decision-making, corporate strategy, and regulatory development. This research contributes original insights by providing up-to-date empirical data for the post-pandemic period, filling a gap in the literature, and offering a comprehensive understanding of the dynamics of insurance company valuation in Indonesia.